Upaya Meningkatkan Penggunaan Ulang App Halodoc: Explorasi Akses Mudah, Penilaian Risiko, dan Sikap Pasien - Fayola Issalillah; Firza Fahriza; Arif Rachman Putra; Didit Darmawan; Rafadi Khan Khayru (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Technology-based health applications are increasingly dominating healthcare services with the emergence of platforms that allow patients to access medical information, doctor consultations, and health-related services online. One application that has emerged is Halodoc, which provides application-based health services in Indonesia. This study aims to analyze the effect of accessibility, risk perception, and patient attitudes on their intention to reuse the Halodoc application. The research method uses a quantitative approach. Questionnaires were distributed to users who had used the Halodoc application. The analysis technique of this research is purposive sampling. The research sample consisted of 130 respondents from the city of Surabaya who had previously consulted using the Halodoc application. The results of the data analysis show that accessibility has a positive and significant effect on the intention to reuse the Halodoc application. The easier it is for patients to access services via the app, the higher their intention to use them again. In addition, perceived risk also has a significant effect on reuse intentions. Patients who feel that using the app is safe and their privacy is protected tend to have a higher intention to use it again. Patient attitudes towards the Halodoc application also have a significant positive impact on reuse intentions. Patients who have a positive view of the benefits and value of this application are more likely to reuse Halodoc services.